Search for Ligands Complementary to the 430-cavity of Influenza Virus Neuraminidase by Virtual Screening - Nilov, Dmitry K.; Schmidtke, Michaela; Makarov, Vadim A.; Švedas, Vytas K. (Supercomputing Frontiers and Innovations, 2022)
An anthrapyrazole derivative STK663786 has been identified as a selective ligand of the socalled 430-cavity of influenza virus neuraminidase at virtual screening of a library of low-molecularweight compounds. It is able to form favorable contacts with hydrophobic residues as well as cationπ interaction and hydrogen bonds with the polar Arg371 residue. The experimentally determined EC₅₀ values have been found to be 19 and 30 µM for viruses H1N1 and H3N2, respectively. Complementarity of STK663786 to the 430-cavity adjacent to the sialic acid binding subsite in the active center of neuraminidase makes this compound a valuable structural fragment at construction of bifunctional inhibitors of the enzyme.